EVALUATION OF TRANSPORT AND STORAGE PERFORMANCE IN THE EUROPEAN UNION - Lukić, Radojko (Economic Outlook, 2022)
The evaluation of transport and storage performance is continuously current, significant and complex. This paper analyzes the performance of transport and storage in the European Union based on the MARCOS method. The research results show that in terms of transport and storage performance, the top five countries in order include: Germany, France, Spain, Italy and Poland. The developed countries of the European Union are therefore in question. The performance of transport and storage is better in Croatia than in Slovenia due to, among other things, the significantly lower overall procurement of goods and services. The improvement of transport performance can be significantly influenced by effective control of analyzed factors (number of companies, number of employees, turnover, total procurement of goods and services, personnel, added value by factor costs and gross operating surplus). The implementation of the concept of sustainable development and digitization of the entire transport and storage business plays a significant role in this.
Keywords: performance; transport; storage; European Union; MARCOS method